2014
DOI: 10.1159/000362169
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Coronary Artery Calcification in Living Kidney Donors: A Follow-Up Study

Abstract: Background: Data on the long-term mortality and morbidity of living kidney donors are scarce. In the general population, coronary artery calcification (CAC) and progression of CAC are predictors of future cardiac risk. We conducted a study to determine the progression of CAC in renal transplant donors. Methods: We used multidetector computed tomography to examine CAC in 75 former renal transplant donors. A baseline and a follow-up scan were performed and changes in CAC scores were evaluated in each subject ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…Altogether, our results indicate that a loss of GFR related to a reduction in nephron mass in the absence of kidney disease does not per se increase at 1 year the calcification risk. These data are in line with recent observations demonstrating that coronary calcium imaging scores are not enhanced and do not progress rapidly in LKDs [33,34] and confirm the observation that uninephrectomy in donors is not equivalent to CKD despite the reduction in GFR and kidney mass [35].…”
Section: Discussionsupporting
confidence: 92%
“…Altogether, our results indicate that a loss of GFR related to a reduction in nephron mass in the absence of kidney disease does not per se increase at 1 year the calcification risk. These data are in line with recent observations demonstrating that coronary calcium imaging scores are not enhanced and do not progress rapidly in LKDs [33,34] and confirm the observation that uninephrectomy in donors is not equivalent to CKD despite the reduction in GFR and kidney mass [35].…”
Section: Discussionsupporting
confidence: 92%
“…25 A significantly lower frequency for maintaining zero CAC (33%) was reported by Alagoz et al in 75 kidney donors. 26 In the current study in a community-based population, we observed that 80% of participants maintained a zero Agatston score (901/1119), not markedly different from prior findings in disease-based studies. Results of our study are consistent with other studies that describe variations in CVD and related health well-being varies within an otherwise low-risk middle-aged population free of CAC.…”
Section: Discussioncontrasting
confidence: 75%
“…Thirty-four articles published results investigating a possible association between calcium and arterial calcification ( Alagoz et al, 2014 ; Arad et al, 1998 ; Billington et al, 2020 ; Chen et al, 2006 ; Criqui et al, 2010 ; Foley et al, 2009 ; Grønhøj et al, 2016 ; Kim et al, 2013 ; Kwak et al, 2014 ; Liang et al, 2021 ; Nam et al, 2017 ; Nielsen et al, 2021 ; Park et al, 2011 ; Park et al, 2016 ; Shin et al, 2012 ; Tuersun et al, 2020 ; Tuttle and Short, 2009 ; Wei et al, 2020 ; Wu et al, 2016b ; Zagura et al, 2011 ; Barbarash et al, 2016 ; Cancela et al, 2012 ; Chai et al, 2017 ; Davaine et al, 2016 ; Diederichsen et al, 2017 ; Donate-Correa et al, 2019 ; Golovkin et al, 2016 ; Liu et al, 2019 ; Masai et al, 2013 ; Pirro et al, 2013 ; Schlieper et al, 2010 ; Torii et al, 2016 ; Awan et al, 2010 ; Razavi et al, 2021 ). Of these studies, nine reported positive associations ( Grønhøj et al, 2016 ; Kwak et al, 2014 ; Nielsen et al, 2021 ; Shin et al, 2012 ; Tuttle and Short, 2009 ; Zagura et al, 2011 ; Diederichsen et al, 2017 ; Golovkin et al, 2016 ; Awan et al, 2010 ) and 25 reported no significant association ( Alagoz et al, 2014 ; Arad et al, 1998 ; Billington et al, 2020 ; Chen et al, 2006 ; Criqui et al, 2010 ; Foley et al, 2009 ; Kim et al, 2013 ; Liang et al, 2021 ...…”
Section: Resultsmentioning
confidence: 99%